Underwater image copyright protection using robust watermarking technique - Methaq Talib Gaata; Mustafa Dhiaa Al-Hassani (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
It became possible to send and reformat underwater images for copyright theft due to the rapid advancement of computer networks and image forgery tools. Acquiring underwater images is dangerous and requires much efforts, expensive imaging equipment, and professional photographers. Therefore, there is an urgent need to develop copyright protection methods to ensure that property rights are not lost. This paper presents a robust watermarking technique that ensures proof of ownership for underwater images, preventing unauthorized individuals from claiming ownership. The suggested watermarking technique's main contribution depends on using the Hough transform in order to find appropriate regions to hide the watermark information within the underwater images. The Hough transform is useful for identifying areas of difficult texture that can be used as a host for watermark information with minimal distortion. Also, the Twofish algorithm has been used to encrypt the watermark information before being hidden in the underwater image. The performance of the suggested watermarking technique is tested by two metrics: quality and robustness. The results show that the suggested method works because of the quality of the images that were made after the watermark was added and because it could withstand the attacks on it.